Evaluation of crude oil asphaltene deposition inhibitors by surface plasmon resonance. (1st August 2020) - Khosravi, Raha; Rodriguez, Cesar; Mostowfi, Farshid; Sieben, Vincent
Abstract: We present a direct method for evaluating the effectiveness of inhibitors on asphaltene deposition from crude oil based on a Kretschmann configuration surface plasmon resonance (SPR) sensor. We demonstrate that shifts in the peak SPR wavelength during titration experiments can be used to compare inhibitors, both by changes to the deposition temporal profile and by changes to the refractive index of the final deposit. We continually measure the SPR peak wavelength throughout the entire titration experiment, starting with that of the neat crude oil and gradually ramping through a pre-defined range of n-heptane to crude oil fractions. After the deposition onset point, asphaltenes precipitate and are deposited onto the sensing surface, which results in an SPR peak wavelength increase as the refractive index of the deposit on the sensing surface increases. The asphaltenes continue to deposit on the surface until the deposit completely fills the SPR field penetration depth. We observe a change in the asphaltene deposition profile and also the final average refractive index of the deposit when inhibitors are added to the neat crude oil and the same titration experiment is conducted. We also qualitatively describe the asphaltene deposition mechanism using SPR spectral data. SPR provides a new and powerful sensing approach for screening and comparing the effectiveness of asphaltene deposition inhibitors.